2019
DOI: 10.1002/zamm.201900009
|View full text |Cite
|
Sign up to set email alerts
|

Review of applications of self‐excited oscillations to highly sensitive vibrational sensors

Abstract: Vibrational sensors with resonators are suited for online monitoring because of their fast response and ability to measure instantly and continuously. Also, their miniaturization realizes much higher resolution. In this review, we begin by discussing sensor resolution based on the natural frequency shift of the resonator. For mass and stiffness sensing, the detection method for the natural frequency shift by self‐excited oscillation is characterized comparing with that by external excitation. Self‐excited osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 69 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…The unique ability to tailor the eigenvectors shape, for example, by tuning the veering or crossing frequencies, may allow to change the position of the specific (nth) beam of the array within the vector from the node where the displacement is close to zero up to locations where the modal amplitude is maximal. This feature could be beneficial in so-called "mode localization" based sensors [5,39,40], where the ratio between the modal amplitudes, rather than the frequency shifts, are monitored.…”
Section: Discussionmentioning
confidence: 99%
“…The unique ability to tailor the eigenvectors shape, for example, by tuning the veering or crossing frequencies, may allow to change the position of the specific (nth) beam of the array within the vector from the node where the displacement is close to zero up to locations where the modal amplitude is maximal. This feature could be beneficial in so-called "mode localization" based sensors [5,39,40], where the ratio between the modal amplitudes, rather than the frequency shifts, are monitored.…”
Section: Discussionmentioning
confidence: 99%
“…measured object or sample. Regarding the way of the detection of frequency shifts, there are some types of vibration mechanism, external excitation [4][5][6], self-excited oscillation [7,8], parametric excitation [9,10], and so on. Also, there are a few methods of driving microcantilever, which are piezoelectrical [11,12], magnetical [13][14][15], and thermomechanical [16][17][18] actuation.…”
Section: Introductionmentioning
confidence: 99%
“…vibratory machines [2], self-excited biped mechanisms [3], vibratory drilling [4], biosensor [5], pipe crawling robots [6], electrostatic field sensing [7], atomic force microscopy [8], vibrational sensors (mass sensor, viscometer, stiffness sensor) [9], nanoscale cutting [10], etc. Babitsky [2] found that the efficiency of many processes in vibratory and percussion machines like displacements of materials and parts, mixing, grinding, batching, separation, etc.…”
Section: Introductionmentioning
confidence: 99%